Laser conduction welding characteristics of dissimilar metals Mg/Ti with Al interlayer. (April 2018) - Zang, Chengwei; Liu, Jinge; Tan, Caiwang; Zhang, Kaiping; Song, Xiaoguo; Chen, Bo; Li, Liqun; Feng, Jicai
Abstract: The immiscible and nonreactive characteristics of Mg/Ti dissimilar metals restrict the metallurgical bonding and reliable joining of them. To solve this problem, the Al interlayer between Mg/Ti was added. The Mg/Ti joint without addition of Al interlayer could not be welded, while relatively acceptable appearance was obtained when adding Al interlayer. The interfacial reaction was improved with the assistance of Al interlayer resulting in metallurgical bonding at the interface. The TiAl3 phase formed at the direct laser irradiation zone. Note that the interfacial reaction layer increased little with the increasing thickness of Al interlayer. The interfacial reaction layer was mainly restricted by dissolution of Ti element. Temperature field and thermodynamic calculation assisted to prove the interfacial reaction at the fusion zone/Ti interface and the formation of TiAl3 . The tensile-shear testing indicated that the maximum tensile-shear force could reach 2230 N/cm (about 81% of that of AZ31B Mg alloy base metal) when the laser power was 2300 W and the thickness of added Al interlayer was 0.05 mm. The tensile-shear force decreased when network structure of Mg17 Al12 precipitated in the weld zone. The fracture path changed from fusion zone/Ti to Mg fusion line when the thickness of Al interlayer exceeded 0.12 mm.